DETERMINASI PENDIDIKAN AGAMA ISLAM DAN POLA ASUH DEMOKRATIS TERHADAP AKHLAK REMAJA - ABIDATUL MARDLIYAH (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
Abstract: This study aims to determine the relationship between Islamic religious education and democratic parenting style with adolescent morals. The subjects of this study were 79 adolescents living in Sumbermulyo, Jogoroto, Jombang Regency. To obtain data on the relationship between Islamic Religious Education and democratic parenting style with adolescent morals, a questionnaire compiled by the researcher was used. To achieve this goal, the data were analyzed by means of regression analysis, as well as by observations and some existing data and documents. Based on the results of data analysis, obtained t count of 5.636 when referred to the value of t table at the significance level of 5% obtained t table value of 1.67 so that t count is greater than t table (5.636 ?1.67), then the results are significant. Thus it can be concluded that, (1) there is a significant positive influence between Islamic Religious Education on adolescent morals in the community of Sumbermulyo, Jogoroto, Jombang Regency; (2) there is a positive effect of democratic parenting on adolescent morals Keywords: Islamic religious education, democratic parenting, adolescent morals